Democracy and Human Development: Conceptualising The Pathways of Influence - Rizki Hegia Sampurna; Chih-Chieh Chou (Journal of Government and Civil Society, 2025)
ThisÂ  article addresses the gap in understanding the causal mechanisms linking democracy to human development. While existing research focuses on correlations or broad linkages, this study conceptualizes specific mechanisms at macro and micro levels, proposing an integrative framework that synthesizes diverse theoretical perspectives. The framework emphasizes the interconnected roles of electoral accountability, civil society, a culture of equality, and good governance in driving human development, offering a nuanced understanding of the democracy-development nexus. The study makes three key contributions: (1) identifying specific causal pathways; (2) providing a foundation for empirical research, particularly through qualitative case studies or process tracing; and (3) highlighting the importance of holistic democratic governance. It concludes that government expenditure on human development sectors, influenced by electoral accountability and good governance, is a plausible mechanism. However, the study acknowledges limitations, such as confounding factors like economic conditions and cultural differences, and calls for future research to empirically test these mechanisms. Methodologically, mixed-methods approaches, combining quantitative analysis with qualitative case studies, are recommended to validate the framework across diverse contexts. By doing so, this study aims to provide actionable insights for policymakers and researchers seeking to enhance human development through democratic governance.Â Artikel ini berupaya mengatasi celah dalam pemahaman tentang mekanisme kausal yang menghubungkan demokrasi dengan pembangunan manusia. Sementara penelitian yang ada fokus pada korelasi atau hubungan luas, studi ini mengkonseptualisasikan mekanisme spesifik pada tingkat makro dan mikro, dengan mengusulkan kerangka kerja integratif yang mensintesis berbagai perspektif teoretis. Kerangka kerja ini menekankan peran keterkaitan antara akuntabilitas elektoral, masyarakat sipil, budaya kesetaraan, dan tata kelola yang baik dalam mendorong pembangunan manusia, memberikan pemahaman yang lebih bernuansa tentang hubungan demokrasi-pembangunan. Studi ini memberikan tiga kontribusi utama: (1) mengidentifikasi jalur kausal spesifik; (2) menyediakan landasan untuk penelitian empiris, terutama melalui studi kasus kualitatif atau penelusuran proses (process tracing); dan (3) menyoroti pentingnya pendekatan holistik dalam tata kelola demokratis. Artikel ini menyimpulkan bahwa pengeluaran pemerintah di sektor pembangunan manusia, yang dipengaruhi oleh akuntabilitas elektoral dan tata kelola yang baik, merupakan mekanisme yang memungkinkan. Namun, studi ini juga mengakui keterbatasan, seperti faktor pengganggu (confounding factors) seperti kondisi ekonomi dan perbedaan budaya, serta menyerukan penelitian lebih lanjut untuk menguji mekanisme ini secara empiris. Secara metodologis, pendekatan metode campuran (mixed-methods), yang menggabungkan analisis kuantitatif dengan studi kasus kualitatif, direkomendasikan untuk memvalidasi kerangka kerja ini di berbagai konteks. Dengan demikian, studi ini bertujuan untuk memberikan wawasan yang dapat ditindaklanjuti bagi pembuat kebijakan dan peneliti dalam upaya meningkatkan pembangunan manusia melalui tata kelola demokratis.